Suicide kills more peoples than any form of violence - Sadek, A; Anam, AMA; Rashid, MSA; Akber, EB; Khan, NT (Mediscope, 2019)
“Suicide is a tragic global public health problem. Globally, WHO said the death toll from suicide – at almost one million people per year – accounts for half of all violent deaths. Estimates suggest fatalities could rise to 1.5 million by 2020. Recently it’s been a great concern to examine suicide trends among teenage people. They are emotional and can’t tolerate difficult situation. They think it is a permanent problem so suicide is the only solution. Last year (2017) large number of SSC candidate students committed suicide in different districts due to not getting expected result. So this is the time to create awareness among society and also family support to child, otherwise no one can predict it. One day these victims will be their family members. Our review articles focuses on causes, risk factors and prevention of teenage suicide in country. Mediscope Vol. 6, No. 2: Jul 2019, Page 87-92